WORK READINESS OF INDONESIAN STUDENTS: PHENOMENOLOGICAL STUDY OF INTERNATIONAL INTERNSHIP EXPERIENCE AND WORK MOTIVATION IN TAIWAN - Andriana Indah Kurniawati Laia; Bayu Ade Prabowo (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study explores how international internship experiences in Taiwan shape work readiness and work motivation among Indonesian business students from STIEPARI Semarang. Limited research examines the phenomenological dimensions of how students subjectively experience international internships, particularly in the Indonesia-Taiwan educational mobility pathway.METHODOLOGY - A qualitative phenomenological design employed purposive sampling of seven STIEPARI students: three currently interning in Taiwan and four returned to Indonesia. Data were collected through semi-structured interviews (45-60 minutes) guided by 25 open-ended questions across nine thematic domains. Braun and Clarke's (2006) six-phase thematic analysis was applied, with trustworthiness established through member checking, thick description, audit trails, and reflexivity journaling.FINDING - Five themes emerged: (1) international internship as transformative cultural immersion; (2) multidimensional skill development through authentic work engagement; (3) cross-cultural challenges as catalysts for resilience and adaptability; (4) work motivation evolution from extrinsic to intrinsic orientations; and (5) enhanced work readiness integrating competencies with psychological confidence and global cultural intelligence. Findings validate Experiential Learning Theory and Self-Determination Theory while extending work readiness frameworks to include global competence as a critical fifth dimension, offering implications for higher education institutions designing international programs